Kia Corporation´s equity valuation - Vörös, Miklós Sándor (2021)
This dissertation presents an equity valuation of a South Korean automotive company, Kia Corporation. The company has recently gone through a brand relaunch and has started to implement its new mid-to long term strategy, called ‘Plan S’, which aims to establish a leadership position in the automotive industry. The goal of the valuation is to determine Kia’s fair share price and provide a buy, hold, or sell recommendation as of the 30th of April 2021. To justify the assumptions, an overview of Kia Corporation is presented, as well as a sector outlook and a macroeconomic outlook, including the company’s main risks and opportunities. All considered, Kia has a huge potential, however, it is not yet reflected in its share price. In the valuation process, three different methods are applied: The Discounted Cash Flow Model (DCF), the Dividend Discount Model (DDM), and the Relative Valuation. To arrive at the final target share price, a weighted average is used, with 90% allocated to DCF, 0% to DDM, and 10% to Relative Valuation. As a result, the fair share price is 120,455 KRW which shows a 56% upside compared to its current share price of 77,000 KRW. Consequently, my recommendation for Kia Corporation is a strong buy.